The association of exercise test variables with long-term mortality in patients with chronic Chagas disease - Silva, Rudson S.; Mendes, Fernanda S. N. S.; Fleg, Jerome L.; Rodrigues Junior, Luiz F.; Vieira, Marcelo C.; Xavier, Isis G. G.; Costa, Henrique S.; Reis, Michel S.; Mazzoli-Rocha, Flavia; Costa, Andrea R.; Holanda, Marcelo T.; Veloso, Henrique H.; et al. (Frontiers in Medicine, 2022)
Background The identification of variables obtained in the exercise test (ET) associated with increased risk of death is clinically relevant and would provide additional information for the management of Chagas disease (CD). The objective of the present study was to evaluate the association of ET variables with mortality in patients with chronic CD. Methods This retrospective longitudinal observational study included 232 patients (median age 46.0 years; 50% women) with CD that were followed at the Evandro Chagas National Institute of Infectious Diseases (Rio de Janeiro, Brazil) and performed an ET between 1989 and 2000. The outcome of interest was all-cause mortality. Results There were 103 deaths (44.4%) during a median follow-up of 21.5 years (IQR 25–75% 8.0–27.8), resulting in 24.5 per 1,000 patients/year incidence rate. The ET variables associated with mortality after adjustments for potential confounders were increased maximal (HR 1.02; 95% CI 1.00–1.03 per mmHg) and change (HR 1.03; 95% CI 1.01–1.06 per mmHg) of diastolic blood pressure (DBP) during ET, ventricular tachycardia at rest (HR 3.95; 95% CI 1.14–13.74), during exercise (HR 2.73; 95% CI 1.44–5.20), and recovery (HR 2.60; 95% CI 1.14–5.91), and premature ventricular complexes during recovery (HR 2.06; 1.33–3.21). Conclusion Our findings suggest that ET provides important prognostic value for mortality risk assessment in patients with CD, with hemodynamic (increased DBP during exercise) and electrocardiographic (presence of ventricular arrhythmias) variables independently associated with an increased mortality risk in patients with CD. The identification of individuals at higher mortality risk can facilitate the development of intervention strategies (e.g., close follow-up) that may potentially have an impact on the longevity of patients with CD.